THE ANALYSIS OF THE EMPLOYEE’S JOB SATISFACTION AND PERFORMANCE IN PRIVATE AGRICULTURAL COMPANY - Yassirly Amridha; Mahra Arari Heryanto; Bobby Rachmat Saefudin; Fitri Awaliyah (Universitas Garut, 2019)
This study aims to analyse the level of gardeners’ satisfaction and performance in PT Trisna Naga Asih which is located in Cijambe village, Subang district. This research was a quantitative research with survey methods. The samples are 62 gardeners of PT Trisna Naga Asih. The data analysis used was descriptive analysis by index analysis of Three Box Method. The result of this study indicates that the level of employee’s work and performance are classified as moderate. Job satisfaction is dominated by some supervision answer, the opportunities to progress and working conditions. While the employees’ performance is classified as high when answering cost effectiveness, moderate in the relationship between employees and low in quantity, but overall is classified as moderate. The suggestion that can be given are increasing wages, increasing work facilities, monitoring and improving coordination and openness between employees and the company